Levinas e a reconstrução da subjetividade ética aproximações com o campo da educação - MIRANDA, José Valdinei Albuquerque (2016)
This article aims to discuss the concept of subjectivity in its relation to otherness in education, based on the philosophical thought of Emanuel Levinas. First, it presents the discussion of subjectivity in modern philosophy, and his way of conceiving it as an ideal of free and sovereign subject. Then it develops a critical analysis that problematizes the alleged sovereignty of the subject and reconstructs a new ethical subjectivity, located in the condition of hostage, capable of accommodating the irreducible alterity of the other as an idea of infinity. In the context of the reconstruction of subjectivity, the study establishes approaches to the field of education, emphasizing the educational experience as an ethical event par excellence.